The Impact of Antiretroviral Therapy on Malaria Parasite Transmission - Azevedo, Raquel; Mendes, António M.; Prudêncio, Miguel (Frontiers in Microbiology, 2020)
Co-endemicity between human immunodeficiency virus and Plasmodium parasites, the causative agents of Acquired Immunodeficiency Syndrome and malaria, respectively, occurs in several regions around the world. Although the impact of the interaction between these two organisms is not well understood, it is thought that the outcome of either disease may be negatively influenced by co-infection. Therefore, it is important to understand how current first-line antiretroviral therapies might impact Plasmodium infection in these regions. Here, we describe the effect of 18 antiretroviral compounds and of first-line ART on the blood and sporogonic stages of P. berghei in vitro and in vivo. We show that the combination zidovudine (AZT) + lamivudine (3TC) + lopinavir/ritonavir (LPV/r), employed as first-line HIV treatment in the field, has a strong inhibitory activity on the sporogonic stages of P. berghei, and that several non-nucleoside reverse transcriptase inhibitors (NNRTIs) have a moderate effect on this stage of the parasite’s life cycle. Our results demonstrate the impact of current first-line ART on Plasmodium infection and identify potential alternative therapies for HIV/AIDS that might impact malaria transmission.